IMPLEMENTATION OF THE EDAS METHOD TO DETERMINE YOUTUBE CONTENT WORTH WATCHING FOR CHILDREN’S - Yuan Sa'adati; Fahmi Syuhada; M. Afriansyah; Herliana Rosika; Joni Saputra (Jurnal Teknik Informatika (Jutif), 2023)
Youtube is a platform for watching and sharing videos. Even today, Youtube allows a lot of information that is inappropriate for children to see and watch. This is due to the large number of videos containing violence, sex, or other inappropriate content that are dangerous to watch by children who don’t know the difference between good and bad. This situation can cause anxiety and panic in parents because they are not able to continuously supervise their children. The decision support system is a system that can help someone in making a decision. With the decision support system, it is hoped that it can help parents monitor their children’s Youtube viewing. Data analysis was carried out using the EDAS method by comparing Youtube content with one another based on six criteria, namely not containing violence, not containing harsh words, not containing pornographic elements, educating, entertaining, and creative. The EDAS method is a selection method based on the normalized values of the weights and the distance between positive and negative solutions. Of the 15 Youtube content, there are 5 recommended Youtube content to watch. The 5 Youtube content with the highest rankings are Cocomelon (0.189), Upin & Ipin (0.150), Hey Tayo and Pada Zaman Dahulu Kala (0.101), and Nussa Official (0.063)